Using of hydrogel dressing in the treatment of chronic wounds - Sopata, Maciej; Szewczyk, Maria T.; Zaporowska-Stachowiak, Iwona; Mościcka, Paulina; Jawień, Arkadiusz (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2021)
It has been clinically proven that modern hydrogel wound dressings that balance wound moisture significantly reduce pain levels and at the same time accelerate the healing process. In recent years, the focus in treating wound infections has shifted from antibiotics to antiseptics in combination with modern dressings, including gel dressings, due to the growing number of MDRO. Hydrogel dressings are an efficient and easy-to-apply product supporting wound healing processes; in addition, hydrogel dressings containing antimicrobial substances, such as octenidine, are effective in preventing and counteracting infections. In this review, we compare octenidine- based gels with other available antimicrobial therapies, taking into account both the results of in vivo clinical studies and ex vivo molecular studies.